Über die Gründe global zunehmender Armut und Ungleichheit – oder warum der „Matthäus Effekt“ vorherrscht - Wade, Robert Hunter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
A widespread neoliberal argument tells us, that increasing globalisation has caused a considerable decrease in world poverty during the last two decades. In the article it is shown, that this result depends on the method of measurement, and on the countries which are considered as “globalisers”. In contrast to such doubtful results, it is argued that the structures of world economy and the “primacy project” of the USA support increasing global inequality, a worldwide “Matthew Effect”, ‘to him that hath, shall be given’.